Psychodidactic features of digital technologies for professional development of an adult’s personality within the framework of additional vocational education - L. Ye. Pautova (Вестник университета, 2025)
The relevance of the study is due to the fact that digital transformation of vocational education requires revision and elaboration of digital educational technologies psychodidactics, particularly in adult learning. The purpose of the study is to determine the psychodynamic features of digital technologies for professional development of adult personality within the framework of additional vocational education. The main objectives of the study contributed to the goal achievement: to analyze the scientific and practical literature on the research issue; to identify the psychodynamic features of digital technologies in adult learning; to determine the relationship of digital technologies of vocational learning and self-development of adult personality on the basis of integration of digital didactics, andragogy, and psychodynamic. Research methods are theoretical and system-logical analysis of digital technologies for adult personality development, practical analysis and synthesis, and results generalization method. The novelty of the study lies in the fact that the promising digital technologies for professional development of a modern worker’s personality and their distinctive features (target orientation, reliability, and openness), contributing to personal and professional development of adults and psychodidactic transformation of the digital educational environment of additional vocational education, have been identified. The literature on the issues of psychodidactics of vocational education, digital didactics, and psychodidactics, and on the issues of digital technologies application in training and development of adult learners has been analyzed. The peculiarities of open Internet resources that allow to determine the educational potential of digital technologies have been revealed. Psychodidactic elements of digital technologies for professional development of adult personality have been revealed. The system-structural interrelationships of digital and traditional educational technologies for professional learning and self-development of adult personality have been determined.